Correlation of maternal platelet to lymphocyte ratio, neutrophil to lymphocyte ratio, C- reactive protein with gestational age at delivery and fetal outcome - A prospective observational study from tertiary care centre - Mrinalini Kannan; Sajeetha Kumari R; Vinodhini Shanmugham (Elsevier, 2024)
Background: Economic burden of preterm births can be reduced by screening and treating them at the early stage. The mechanism behind preterm birth is not clear and therefore there is no effective globally accepted treatment. Screening methods were mainly based on the previous obstetric history of the pregnant woman. Evidences indicate inflammatory markers such as neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) might be potential predictors of preterm deliveries. This study was aimed to determine the relationship between preterm births and NLR, PLR and CRP levels in a singleton pregnant woman. Material and methods: This prospective observational study was conducted in the Department of obstetrics and gynaecology in a tertiary care hospital located at Chengalpattu, Kanchipuram, Tamil Nadu with an objective to determine the relationship between inflammatory markers and the foetal outcome among singleton pregnant woman.The Study period was from August 2022 to July 2023 for a period of 1 year. This study enrolled pregnant women between 28 and 32 weeks of gestation attending regular antenatal clinic and those willing to give informed consent. Results: There was mean difference between both the groups in terms of WBC count (white blood cell) [11.87(±3.7) in pre term vs. 10.71(±2.76) in term], platelet count [262.7(±59.1) in pre term vs. 234.5(±73.6) in term], Absolute lymphocyte count [194.0(±93.6) in preterm vs. 203.8(±63.3) in term], Neutrophil lymphocyte ratio (NLR) [6.3(±2.8) in preterm vs. 3.7(±0.8) in term] and platelet lymphocyte ratio (PLR) [165.1(±87.9) in pre term vs. 120.7± (39.1) term] and all these difference were found to be statistically significant (p-value <0.05*). Conclusion: This prospective observational study deduced the association between the inflammatory markers and preterm delivery in a singleton pregnant woman. Rise in inflammatory parameters like neutrophil lymphocyte ratio, platelet lymphocyte ratio and C-reactive protein proved to be useful in predicting spontaneous preterm labour (before 37 weeks of gestation).